Official Duties and Contextual Responsibilities Contingent to the Prophetic Sīrah - Tariq Aziz; Manj, Muhammad Shahbaz (Journal of Islamic and Religious Studies, 2019)
Rights of Holy Prophet Muḥammad (P.B.U.H) have been studied from various perspectives. This paper reviewing the extant research on the subject; identifies the duties of government officials from the referred side. It concludes that Prophet Muḥammad (P.B.U.H) is the most benefactor and humanitarian to mankind in the word. In this context only those Govt. officials can be considered true in their claim of love for Prophet Muḥammad (P.B.U.H) who adhere to his teachings, concerning ability of one’s position, piety, liability, morality and uprightness and those who refrain from being footloose and profligate, and free themselves from the hunger of wealth and status, censoriously evaluate their deeds, keep an eye on the life hereafter and accountability. Moreover, those who hold justice and avoid dishonesty and bias are true according to the teachings of Islam. Without such qualities and characteristics claim of love is just deceit and forgery.